Development of Baluran Ecotourism Learning Media Assisted by Google Sites on Biodiversity Materials - Muhammad Risky Yanuar; Tuti Mutia; Yusuf Suharto; Ike Sari Astuti (CV Bumi Spasial, 2025)
Technological developments in the industrial revolution 4.0 era are progressing rapidly, as is the world of education. Technological advances in the world of education are increasingly sophisticated by utilizing media as a learning aid. This study aims to develop a digital learning media, specifically the Baluran Ecotourism media supported by Google Sites, and to evaluate its feasibility and practicality in the context of geography education. The research employed the ADDIE instructional design model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation, due to its systematic and iterative structure, which allows for continuous feedback and refinement throughout the development process. The data analysis incorporated both qualitative and quantitative descriptive approaches: qualitative analysis was conducted through expert feedback and open-ended responses, while quantitative analysis was based on questionnaire scores collected from validators, students, and teachers using a Likert-scale instrument. This research instrument is a material validation and media validation questionnaire, then a student and teacher response questionnaire after using the media. implementation was carried out on students and teachers of SMAN 1 Asembagus and received a positive response. The research results showed that material experts obtained results of 86% (very feasible) and media experts obtained results of 78% (very feasible). The results of student responses obtained an average of 87.9% (very practical). So it can be concluded that the Baluran Ecotourism learning media has been validated and is suitable for use by students and teachers in geography learning.